Pengendalian kualitas produk bulk container bag di PT XYZ menggunakan metode Root Cause Analysis - Zidane, Muhammad Azzam; Pulansari, Farida (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research uses the Root Cause Analysis (RCA) method to analyze the main causes of defects in bulk container bag/jumbo bag products at PT The four main types of defects, namely hole body, off-center printing, folded body, and dirt, were identified using the Pareto diagram, with hole body being the highest category (37%). The P-chart shows that the production process is within statistical control limits. Fishbone analysis found five main factors that cause defects: people, materials, machines, methods and work environment. Suggested solutions include employee training, stricter raw material selection, machine maintenance, work environment improvements, and implementation of standard operating procedures. The results of this research provide recommendations for quality improvement to reduce defect levels.